Profiles of theory of mind impairments and personality in clinical and community samples: integrating the alternative DSM-5 model for personality disorders - Lampron, Mireille; Achim, Amélie M.; Gamache, Dominick; Bernier, Allyson; Sabourin, Stéphane; Savard, Claudia (Frontiers in Psychiatry, 2024)
Introduction: Deficits in theory of mind (ToM)—the ability to infer the mental states of others—have been linked to antagonistic traits in community samples. ToM deficits have also been identified in people with personality disorders (PD), although with conflicting evidence, partly due to the use of categorical diagnoses. The DSM-5 Alternative Model for Personality Disorders (AMPD) provides an opportunity for a more precise understanding of the interplay between ToM abilities and personality pathology. Therefore, the study aims to determine whether and how individuals with diverse ToM profiles differ regarding personality impairment (AMPD Criterion A) and pathological facets (AMPD Criterion B). Method: Adults with PD (n = 39) and from the community (n = 42) completed tests assessing ToM skills and self-reported questionnaires assessing AMPD Criteria A and B. Hierarchical agglomerative and TwoStep cluster analyses were consecutively computed using scores and subscores from ToM tests as clustering variables. Multivariate analyses of variance were subsequently performed to compare the clusters on both AMPD Criteria. Five clinically and conceptually meaningful clusters were found. The most notable differences across clusters were observed for Intimacy and Empathy dysfunctions (Criterion A), as well as the Deceitfulness, Callousness, and Hostility facets from the Antagonism domain and the Restricted affectivity facet from the Detachment domain (Criterion B). Discussion: The results support the association between antagonistic personality facets and ToM deficits. However, clusters showing impairments in ToM abilities did not necessarily exhibit high levels of personality dysfunction or pathological facets, emphasizing that both constructs are not isomorphic. Nevertheless, specific profiles can help refine existing interventions to make them more sensitive and specific to the nature of ToM dysfunctions while considering personality functioning and facets.